PKM Teknologi Fermentasi Pakan Jerami Padi dan Pembuatan Pupuk Organik Pada Kelompok Ternak â€œSato Luwihâ€ Desa Kenderan Kecamatan Tegalalang-Kabupaten Gianyar - I Dewa Nyoman Sudita; Yohanes Parlindungan Situmeang; Kadek Suniasta Amerta (Universitas Warmadewa, 2021)
The provincial government of Bali has continuously encouraged livestock farming communities to form livestock groups especially the cows, through the Simantri program since 2009/2010 and is now known as Sipadu. In addition to this program, livestock groups are also formed independently by livestock farmers spread across Bali, one of which is the â€œSato Luwihâ€ livestock group in Kendran Village, Tegalalang-Gianyar, which requires guidance and assistance in empowering the resources they have, namely livestock and waste produced. The livestock group in Kendran village was only formed in early 2020, where its members have different abilities in raising livestock, both experienced and just starting to learn to raise livestock. Besides that, the existing resources in the form of cattle waste have not been utilized, on the one hand the waste still has the potential to increase group income if it is processed into organic compost. The problems faced by the group and group members are the lack of knowledge in the management of animal feed using rice straw, knowledge of technology for processing cow dung, both faeces and urine into organic fertilizer, and lack of understanding of the use of organic compost fertilizer in the farming system. Therefore, through PKM activities, it is necessary to provide assistance and transfer of applied technology to group members, so that the utilization of their resources can be utilized optimally. The methods used in this PKM activity are: observation and group discussion, counseling, and field practice. Group discussions were carried out by involving group administrators to determine the provision of activity materials and implementation schedules. Counseling was given to all group members about making fermented straw feed and making organic cow manure. While the practice is carried out directly by group members, and the results have been evaluated. The results of the PKM show that group members have been able to make fermented straw as animal feed and utilize livestock dung waste into organic fertilizer, so as to maintain the cleanliness of the cage environment. From this PKM activity, it can be concluded that there has been a change in the behavior of group members, namely knowledge and skills, while changes in attitude still need to be carried out by field observations.